The effect of pollution on the livestock management, microbial evaluation, health risks, and HPLC analysis of aflatoxins in animal meat and organs - Alharthi, Sarah; Uguru, Hilary; Akpokodje, Ovie I.; Sami, Rokayya; Alqurashi, Mohammed; Aloufi, Salman; Al-Otaibi, Saad A.; Albaqami, Jawaher J.; Zarah, Rowa K.; Hamdi, Hamida; Kadi, Roqayah H.; Almasoudi, Suad H.; et al. (Frontiers in Sustainable Food Systems, 2025)
Free-range animal rearing system is a practical approach to monitor terrestrial pollution in livestock management and public health. This research evaluated the potential health hazards, linked with heavy metals (HMs) and microbial pollution of forage and soil, ingested by free-range domestic animals (cattle, and goats) and wild animals, as well as their subsequent impact on human health. Eighty vegetation samples, 40 soil samples, and a total of 240 animal samples (120 muscle tissues and 120 livers) were extensively collected from the Guinea savannah and rainforest regions. The specimens' heavy metals (Cd, Pb, As, Cr, Ni, Zn, and Cu) concentrations and microbial contamination were determined, in accordance with ASTM and ISO approved guidelines. Remarkably, the HPLC analysis was used to detect the aflatoxins in the animal samples. The results revealed that the vegetation, soil and animal's tissues specimens contained significant amount of HMs and pathogenic microorganisms. Notably, Pb had the maximum concentration, with levels ranging from 1.515 to 1.919 mg/kg and 1.558 to 2.107 mg/kg, respectively, in the animal's muscle and liver samples; while arsenic had the least concentration, which varied from 0.021 to 0.027 mg/kg and 0.022 to 0.037 mg/kg respectively, in the animal's muscle and liver specimens. Though, the values of some of the HMs were quite high, their average concentrations were less than the maximum limits approved by the World Health Organization, for edible food items. Similarly, the results highlighted that the animal specimens exhibited a considerable pathogenic bacteria (≤ 3,760 cfu/g), fungi (≤ 2,940 cfu/g), and aflatoxins (≤ 8.04 ppb) loads. The HMs content and microbial loads were higher in the liver than in the muscle; and the cow tissues recorded the optimal levels of the HMs and pathogens investigated. Although, the health risk indices (hazard index and cancer risk) indicated that the consumption of the animal samples posed inconsequential non-carcinogenic or carcinogenic risk; but the elevated HMs and pathogenic microorganisms' levels documented, depicted the necessity of consistent environmental control and monitoring. This is to prevent the bioaccumulation of toxic HMs and pathogens in the vegetation and animal bodies, along with the associated risks in animal production and the food supply chain.